2022
DOI: 10.7759/cureus.32934
|View full text |Cite
|
Sign up to set email alerts
|

Rare Metallic Allergy Reaction Presentation to Cholecystectomy Surgical Clip

Abstract: Metal allergies have been a growing concern in the general population over the past several decades. Laparoscopic cholecystectomy is the standard treatment for gallbladder diseases such as cholelithiasis and cholecystitis, during which surgical clips composed of metals such as nickel or titanium are often used to clamp the arteries and ducts. These metals are documented to produce hypersensitivity reactions. Here, we present the case of a 53-year-old male patient who successfully underwent laparoscopic cholecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Mozafari et al . [ 16 ] found that allergies secondary to hemoclip placement may cause type IV hypersensitivity symptoms most commonly because of the composition of nickel or titanium in metallic clips. The patient in our case received metal clips and if unnoticed, this may have developed into a larger acute inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mozafari et al . [ 16 ] found that allergies secondary to hemoclip placement may cause type IV hypersensitivity symptoms most commonly because of the composition of nickel or titanium in metallic clips. The patient in our case received metal clips and if unnoticed, this may have developed into a larger acute inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in our case received metal clips and if unnoticed, this may have developed into a larger acute inflammatory process. There is no standardized regulation of allergy testing before procedures and given the high prevalence of metal allergies within the general population at 10%–15%, it remains questionable whether the convenience of using hemoclips versus other materials is beneficial [ 16 ].…”
Section: Discussionmentioning
confidence: 99%